(untitled) (Central Medical College Journal, 2026)
Background: Reconstruction of dorsum of the foot and ankle is challenging due to exposed tendons, nerves, and bones. Sural (SF) and Lateral Supramalleolar flaps (LSF) are commonly used for reliable coverage and functional restoration. Objective: To assess and compare the effectiveness and outcomes of Lateral Supramalleolar and Sural flaps in reconstructing dorsum of foot and ankle defects. Methods: This prospective cohort study at Sylhet MAG Osmani Medical College Hospital was conducted from September 2021 to February 2024, enrolling 30 patients who met the inclusion criteria and were randomly assigned to Group A (Sural, n= 15) and Group B (Lateral Supramalleolar, n= 15). All patients had clinical and Doppler assessments, flap surgery under spinal anesthesia, and outcomes were evaluated at 1, 2, and 3 months using the “Hashmi Flap Outcome Score”. Results: The groups were comparable in age (35.2±13.5 vs. 35.0 ± 11.9 years, p= 0.966) and gender (p= 0.321). Trauma was the leading cause of defects (83.3%, p=0.041), with right-sided defects more frequent in Group B (56.7%, p=0.032). Defect size (7.43 ± 0.84 vs. 7.07±0.70 cm, p=0.206) and flap size (8.08±0.92 vs. 7.65±0.71 cm, p=0.16) were similar. Sural flaps were longer (9.80±0.98 vs. 9.13±1.03 cm, p=0.041), but Lateral Supramalleolar flaps required shorter operative time (112.2±4.7 vs. 115.8±5.7 minutes, p=0.038). Flap survival was 100% in both groups. Postoperative complications were minimal. Functional outcomes favored Lateral Supramalleolar flaps, with more patients achieving excellent recovery (86.7% vs. 53.3%, p=0.029) and higher HFOS scores (19.6±1.2 vs. 18.5±1.9, p=0.043).Conclusion: The LSF provides shorter operative time and superior functional outcomes, making it a preferable option for dorsum of foot and ankle defect reconstruction. Central Medical College Journal Vol 9 No 2 July 2025 Page: 91-95